2019
DOI: 10.1038/s41574-019-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Addressing gaps in care of people with conditions affecting sex development and maturation

Abstract: Differences of sex development (DSD) are defined as conditions with discrepancies between chromosomal, gonadal and phenotypic sex. In congenital hypogonadotropic hypogonadism (CHH), a lack of gonadotropin activity results primarily in the absence of pubertal development with prenatal sex development being (almost) unaffected in most patients. To expedite progress in the care of people affected by DSD and CHH, the European Union has funded a number of scientific networks. Two Actions of the Cooperation of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…(c) Biostatistics requires large sample sizes mostly not available in rare disorders such as DSD. Related to this, we would like to emphasize the need for multidisciplinary teams of medical specialists and researchers to implement multicenter collaborations by using well-accredited international registries such as the I-DSD Registry [55] and the European Reference Network for Rare Endocrine Diseases (EndoERN) [56].…”
Section: Perspectives and Pitfallsmentioning
confidence: 99%
“…(c) Biostatistics requires large sample sizes mostly not available in rare disorders such as DSD. Related to this, we would like to emphasize the need for multidisciplinary teams of medical specialists and researchers to implement multicenter collaborations by using well-accredited international registries such as the I-DSD Registry [55] and the European Reference Network for Rare Endocrine Diseases (EndoERN) [56].…”
Section: Perspectives and Pitfallsmentioning
confidence: 99%
“…This involves designing it to comply with international standards of quality, structure and content, access control, and also adopting common methods and processes for information/patient discoverability, sharing and federation with other registries. Thereby, users can more easily compare, pool, and analyse patient datasets, using sufficient numbers of cases for meaningful clinical research and public health purposes in areas identified as high priority by the DSD community [36]. Going forward, it will become particularly important for the I-DSD and I-CAH registries to maximise their quality [18] and increase the participation of patients and professionals in activities that are aimed at improving clinical care as well as our knowledge of these conditions A high quality disease registry also requires clear governance structures and scrutiny and the effort involved in providing this is often under-estimated.…”
Section: Future Direction-quality Fair Values Inclusion and Susmentioning
confidence: 99%
“…From a medical point of view only few forms of DSD require acute medical action. Nevertheless, there is a need for medical treatment in many respects, which, however, can vary greatly depending on the diagnosis, age, and personal needs [3]. First and foremost, medicine has the task of confirming a diagnosis and analyzing possible consequences of the variant gender development (e.g., comorbidities, hormonal peculiarities).…”
Section: Needs For Changing Health Care In Dsdmentioning
confidence: 99%
“…In the last decades, DSDs have undergone enormous changes in general and medical perception, as well as societal acceptance and medical care [2]. In this paper, we will outline, how the increasing demand from people with DSD, but also from health care professionals and the general public has changed established clinical practices for the management of patients within the health care systems [3,4]. In 2005, an international consensus conference was held, which received wide acceptance for its change in nomenclature and advice for management of the conditions [1].…”
Section: Introductionmentioning
confidence: 99%